Understanding the association between neighborhoods and adolescent sleep: Evidence from Add Health - Sam J. Neally; Breanna J.P. Rogers; Yangyang Deng; Mohammad Moniruzzaman; Qian Xiao; Kosuke Tamura (Sleep Epidemiology, 2024)
Introduction: Research suggests that perceived neighborhood social environments (PNSE) may contribute to gender and race/ethnicity-based sleep disparities. Our study aimed to examine associations between PNSE factors and adolescents’ sleep patterns. As a secondary aim, we examined how gender and race/ethnic groups might moderate these associations. Method: Data came from the National Longitudinal Study of Adolescent to Adult Health (n = 5158; mean age=15.34 years). Four self-reported sleep outcomes were created: 1) sleep duration (hours/night), 2) short sleep (≥8 h [reference] vs <8 h), 3) parental set bedtime (10:00PM/earlier [reference] vs by 11:00PM vs by/after 12:00AM), and 4) sleep satisfaction (enough sleep [reference] vs not enough sleep). PNSE included total scores for contentedness, social cohesion, and safety. Weighted linear and generalized logistic regressions were used to examine the relationships between each PNSE factor and sleep outcomes, adjusting for covariates. Associations were stratified by gender and race/ethnicity, separately. Results: Neighborhood contentedness was associated with longer sleep duration and lower odds of short sleep, parental set bedtime by/after 12:00AM, and not enough sleep. Neighborhood social cohesion was related to lower odds of a parental set bedtime by/after 12:00AM. Neighborhood safety was related to lower odds of short sleep and not enough sleep. Gender and race/ethnic-specific results were mixed. Conclusion: Positive perceptions of neighborhood social environments served as a protective factor against adverse sleep outcomes among adolescents. Efforts to improve adolescent sleep should consider the role of the neighborhood social context, gender, and racial and ethnic groups.